Sistem Monitoring Siswa Pada SD Methodist-5 Kota Pagar Alam Berbasis Web - Siti Aminah (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2017)
Student Monitoring System is a method or system that aims to monitor the pattern of student development in school. Growing advances in information technology today, schools need to promote themselves through the school website so that people can access all school information easily, especially to monitor the development of children in school. System development method used in the design of Student Monitoring System is to use waterfall method or waterfall.With this student monitoring system, the guardian of student can know result of student learning evaluation which have been reached in school like student development which is result of evaluation of study of per-week and student value which is result of evaluation of study per-semester.So, it is expected that the guardians can be more easily in monitoring the development of their children in school so that the guardians can know the results of student learning evaluations that have been achieved in school.